Bifurcations in Scientific Careers - Hannu Koskinen (Perspectives of Earth and Space Scientists)
Abstract Life is a chaotic nonlinear dynamical system, so is of course the scientific life as well. Due to external perturbations the trajectory of any scientific career goes through several unstable points and may bifurcate to unexpected directions. I discuss a few critical points based on my own experience as a space scientist throughout my professional career. While my examples are certainly quite typical, the trajectories after the bifurcations are always individual. The advice I wish to give to a young scientist: Watch your opportunities and be well‐prepared.